Lone wolf terrorism: understanding the growing threat - Simon, Jeffrey D. (Prometheus Books, 2016)
Introduction -- The growing threat of lone wolf terrorism -- Who are the lone wolves? -- Why lone wolves are so dangerous -- Where are the women? -- Lone wolf assassins -- Strategies for dealing with lone wolf terrorism -- Uncovering the lessons learned -- A look toward the future